National health inequality monitoring: current challenges and opportunities - Ahmad Reza Hosseinpoor; Nicole Bergen; Anne Schlotheuber; Ties Boerma (Taylor & Francis Group, 2018)
National health inequality monitoring needs considerably more investment to realize equity-oriented health improvements in countries, including advancement towards the Sustainable Development Goals. Following an overview of national health inequality monitoring and the associated resource requirements, we highlight challenges that countries may encounter when setting up, expanding or strengthening national health inequality monitoring systems, and discuss opportunities and key initiatives that aim to address these challenges. We provide specific proposals on what is needed to ensure that national health inequality monitoring systems are harnessed to guide the reduction of health inequalities.